Morphological characteristics of the lungs and assessment of specific blood immune parameters in guinea pigs during the course of experimental pneumonia - Ivankiv , O.L.; Chelpanova , I.V.; Regeda , M.S. (Морфологія / Morphologia / Morfologìâ, 2026)
Pneumonia is an acute inflammatory lung disease. Despite extensive experimental and clinical research, it remains a significant medical challenge. Aim. To investigate the features of morphological changes in the lungs, as well as the levels of T- and B-lymphocytes and circulating immune complexes in the blood serum of guinea pigs during the development of experimental pneumonia (EP) on days 7, 14, and 21 of the experiment. Methods. An experimental pneumonia model was established in 39 guinea pigs weighing 180–230 g. The animals were anesthetized via chloroform inhalation in a desiccator, followed by combined intranasal and inhalation administration of Staphylococcus aureus within a specifically designed chamber. Morphological examination was performed to verify pulmonary inflammation, and blood T- and B-lymphocyte counts were determined across four experimental groups. Results and conclusion. The research findings demonstrated that during the progression of experimental pneumonia (days 7, 14, and 21), there was a statistically significant decrease in cellular immunity parameters, starting from the 7th day of the study. Changes in the humoral immune status, specifically blood B-lymphocyte levels, were also observed in the experimental animals. he progression of EP is characterized by a significant elevation of circulating immune complexes levels in the blood serum of guinea pigs on the specified experimental days; this, coupled with increased B-lymphocyte counts, suggests activation of the humoral immune response. At the observed time points (days 7, 14, and 21), experimental pneumonia is associated with a gradual decline in T-lymphocytes, indicating potential suppression of cellular immunity alongside a statistically significant increase in B-lymphocytes.